ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PRODUK ASURANSI (Studi Kasus Produk Sinarmas MSIG life Link 88 pada PT.Asuransi Jiwa Sinarmas MSIG life Cabang Ambon)â€ - Jancen Roland Patty (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2018)
This study aims to empirically examine the effect of product factors, price factors, promotion factors, people and service process factors on consumer purchasing decisions in choosing Smile Link 88 products at PT. Sinarmas Life Insurance MSIG life Ambon Branch. This research is empirical research, with the sampling technique used is purposive sampling. The analysis used is multiple regression analysis with the least squares equation and hypothesis testing using t-statistics to test the coefficient of partial regression and F-statistics to influence the effect together with a confidence level of 5%.The results of the granting show that, in terms of product factor have a significant effect on consumer purchasing decisions in choosing Smile Link 88 products, the price factor has a significant effect on consumer purchasing decisions in choosing Smile Link 88, promotion factors have a significant effect on Consumer purchasing decisions in choosing Smile Link 88 products, people factors have a significant effect on consumer purchasing decisions in choosing Smile Link 88 products and service process factors (process) have a significant effect on consumer purchasing decisions in choosing Smile Link 88 products at PT Life Insurance SinarmasMSIG life Ambon Branch.